Adding pioglitazone to insulin containing regimens in type 2 diabetes: systematic review and meta-analysis. - Christine Clar; Pamela Royle; Norman Waugh (PLoS ONE, 2009)
Background Type 2 diabetes is treated in a stepwise manner, progressing from diet and physical activity to oral antidiabetic agents and insulin. The oral agent pioglitazone is licensed for use with insulin when metformin is contraindicated or not tolerated. This systematic review and meta-analysis investigates the extent to which adding pioglitazone to insulin-containing regimens produces benefits in terms of patient-relevant outcomes. Methodology/principal findings Medline, Embase, and the Cochrane Library were searched for randomised controlled trials comparing pioglitazone in combination with any insulin-containing regimen in comparison with the same insulin regimen alone in patients with type 2 diabetes. Outcomes investigated included HbA1c, hypoglycaemia, weight, and adverse events. Studies were selected, assessed and summarised according to standard systematic review methodology and in a meta-analysis. We included eight trials that examined the benefits of adding pioglitazone to an insulin regimen and studied a total of 3092 patients with type 2 diabetes. All studies included patients with previously inadequate glucose control. Trial duration was between 12 weeks and 34.5 months. The trials used pioglitazone doses of up to 45 mg/day. In our meta-analysis, the mean reduction in HbA1c was 0.58% (95% CI: -0.70, -0.46, p<0.00001). Hypoglycaemic episodes were slightly more frequent in the pioglitazone arms (relative risk 1.27; 95% CI: 0.99, 1.63, p = 0.06). Where reported, HDL-cholesterol tended to be increased with pioglitazone. Patients on pioglitazone tended to gain more weight than those who were not, with an average difference of almost 3 kg. Peripheral oedema was more frequent in the pioglitazone groups. None of the studies reported on fractures in women, and data on cardiovascular events were inconclusive, with most studies being too short or too small to assess these long-term outcomes. Conclusions/significance When added to insulin regimens, pioglitazone confers a small advantage in terms of HbA1c in type 2 diabetes patients with previous inadequate glucose control, but at the cost of increased hypoglycaemia and weight gain. Other considerations include the risk of heart failure, fractures in women, a reduced insulin dose, and the net financial cost.